Analysis of Lipoasiprated Following Centrifugation: Wet Versus Dry Harvesting Technique. Issue 6 (September 2016) - Agostini, Tommaso; Spinelli, Giuseppe; Perello, Raffella; Bani, Daniele; Boccalini, Giulia
Abstract : Background: The success of lipotransfer strongly depends on the harvesting, processing, and placement of the lipoaspirated samples. This study was designed to assess the histomorphometric characteristics and viability of fat harvested using different techniques (wet and dry) following centrifugation, as described by Coleman. Methods: The study enrolled 85 consecutive, nonrandomized, healthy patients from March 2010 to December 2014 (45 males and 40 females). The mean age was 40 years (range, 18–59 years), and the mean body mass index was 25.8 (range, 24–32). The authors performed a histological analysis (hematoxylin/eosin), morphometry (ImageJ 1.33 free-share image analysis software), and a viability assessment (Trypan Blue exclusion test; Sigma-Aldrich, Milan, Italy) of the lipoaspirated samples. Results: The hematoxylin and eosin-stained sections exhibited similar features; in particular, clear-cut morphological signs of adipocyte disruption, apoptosis, or necrosis were not detected in the examined samples. Morphometry confirmed the visual findings, and the values of the mean surface area of the adipocyte vacuoles were not significantly different. Additionally, the adipocyte viability was not significantly different in the analyzed fat tissue samples. Conclusions: The results from this study showed, for the first time, that there is not a reduction in the viability of fat grafts harvested with the dry or wet technique following centrifugation according to Coleman technique. Both methods of fat harvesting collect viable cells, which are not influenced by standard centrifugation. The fat grafts harvested and processed by this technique could be used in clinical settings without increasing the reabsorption rate. Level of Evidence: V